Stromal Cell-Derived Factor 1 Plasmid Regenerates Both Smooth and Skeletal Muscle After Anal Sphincter Injury in the Long Term. Issue 12 (December 2017) - Sun, Li; Kuang, Mei; Penn, Marc; Damaser, Margot S.; Zutshi, Massarat
Abstract : BACKGROUND: Regenerating muscle at a time remote from injury requires re-expression of cytokines to attract stem cells to start and sustain the process of repair. OBJECTIVE: We aimed to evaluate the sustainability of muscle regeneration after treatment with a nonviral plasmid expressing stromal cell-derived factor 1. DESIGN: This was a randomized study. SETTINGS: The study was conducted with animals in a single research facility. INTERVENTIONS: Fifty-six female age-/weight-matched Sprague–Dawley rats underwent excision of the ventral half of the anal sphincter complex. Three weeks later, rats were randomly allocated (n = 8) to one of the following groups: no treatment, 100 μg of plasmid encoding stromal cell-derived factor 1 injected locally, local injection of plasmid and 8 × 10 5 bone marrow–derived mesenchymal stem cells, and plasmid encoding stromal cell-derived factor 1 injected locally with injection of a gelatin scaffold mixed with bone marrow–derived mesenchymal stem cells. MAIN OUTCOME MEASURES: Anal manometry, histology, immunohistochemistrym and morphometry were performed 8 weeks after treatment. Protein expression of cytokines CXCR4 and Myf5 was investigated 1 week after treatment (n = 6 per group). ANOVA was used, with p < 0.0083 indicating significant differences for anal manometry and p < 0.05 for all other statistical analysis. RESULTS: Eight weeks after treatment, all of the groups receiving the plasmid had significantly higher anal pressures than controls and more organized muscle architecture in the region of the defect. Animals receiving plasmid alone had significantly greater muscle in the defect ( p = 0.03) than either animals with injury alone ( p = 0.02) or those receiving the plasmid, cells, and scaffold ( p = 0.03). Both smooth and skeletal muscles were regenerated significantly more after plasmid treatment. There were no significant differences in the protein levels of CXCR4 or Myf5. LIMITATIONS: The study was limited by its small sample size and because stromal cell-derived factor 1 was not blocked. CONCLUSIONS: A plasmid expressing stromal cell-derived factor 1 may be sufficient to repair an injured anal sphincter even long after the injury and in the absence of mesenchymal stem cell or scaffold treatments. SeeVideo Abstract athttp://links.lww.com/DCR/A451 .